Ulan-Ude Manuscript Kanjur: An Overview, Analysis and Brief Catalogue - Tsyrempilov, Nikolay (Buddhist Studies Review, 2017)
This study investigates the Mongolian manuscript Kanjur preserved at the Center of Oriental Manuscripts and Xylographs of the Institute for Mongolian, Buddhist and Tibetan studies of the Siberian Branch of the Russian Academy of Sciences. The manuscript previously be- longed to the Chesan Buddhist monastery of Central Transbaikalia and was brought to the Buruchkom, a rst academic institute of the Republic of Buryat-Mongolia (Ulan-Ude) by the eminent Buryat writer Khotsa Namsaraev. The manuscript is an almost complete copy of the Ligdan Khan’s Kanjur presumably made in the late sev- enteenth to early eighteenth century in Beijing. The article presents a description, analysis and brief catalogue of Ulan-Ude manuscript Kanjur.
Keywords: Kanjur; Mongolian versions; manuscript; Buddhism; canon